Die skeppingsleer van Filo van Aleksandrie : Joods, Hellenisties, en/of Joods-Hellenisties? - Van Schalkwyk, C. H. J.,1971- (Stellenbosch : Stellenbosch University, 2012)
Tesis (M.A.) -- Universiteit van Stellenbosch, 1994.